Exotic species with explicit noble metal–noble gas–noble metal linkages. Issue 7 (1st February 2018) - Moreno, Norberto; Restrepo, Albeiro; Hadad, C. Z.
Abstract : In Pt2 Ng2 F4 and in [Au2 Ng2 F4 ] 2+, Ng = Kr, Xe, Rn, the noble gas atoms act as links bridging two noble metal atoms. Abstract : We present a study of the isoelectronic Pt2 Ng2 F4 and [Au2 Ng2 F4 ] 2+ species with noble gas atoms (Ng = Kr, Xe, Rn) acting as links bridging the two noble metal atoms. The stability of the species is investigated using several thermodynamic, kinetic and reactivity indicators. The results are compared against [AuXe4 ] 2+, which is thermodynamically unstable in the gas phase but is stabilized in the solid state to the point that it has been experimentally detected as [AuXe4 ](Sb2 F11 )2 (S. Seidel and K. Seppelt, Science, 2000, 290, 117–118). Our results indicate that improving upon [AuXe4 ] 2+, these exotic combinations between the a priori non-reactive noble metals and noble gases lead to metastable species, and, therefore, they have the possibility of existing in the solid state under adequate conditions. Our calculations include accurate energies and geometries at both the CCSD/SDDALL and MP2/SDDALL levels. We offer a detailed description of the nature of the bonding interactions using orbital and density-based analyses. The computational evidence suggests partially covalent and ionic interactions as the stabilization factors.